All-solid-state battery composite positive electrode sheet and preparation method thereof
Patent Information
- Application Number
- CN202611243129.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]针对现有技术的不足,本发明提供了一种全固态电池复合正极极片及其制备方法,该发明要解决的技术问题是:如何通过正极材料颗粒、金属颗粒和固态电解质颗粒的三元混合体系,在不使用导电剂和粘结剂且无需集流体的条件下,利用金属颗粒的延展性变形形成自支撑复合正极极片,解决现有全固态电池正极极片颗粒间界面阻抗大、充放电过程中界面易脱离以及能量密度受限的问题
(1)全固态电池复合正极极片及其制备方法,通过对正极材料颗粒、金属颗粒和固态电解质颗粒依次进行干法混合、压片、热处理和两道次以上的对辊压延,使金属颗粒在无液态溶剂、无导电剂和无聚合物粘结剂条件下发生延展性流动变形并相互连接,形成连续金属网络,同时包裹住全部的正极材料颗粒和固态电解质颗粒,制得自支撑的复合正极极片薄片。该方法省去了溶剂处理环节和聚合物粘结剂的使用,简化了工艺流程,降低了生产成本。
Smart Images

Figure CN122991982A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of all-solid-state battery technology, specifically to an all-solid-state battery composite positive electrode sheet and its preparation method. Background Technology
[0002] Solid-state batteries are considered a crucial next-generation energy storage technology due to their high safety and high energy density. The manufacturing process of the positive electrode has a decisive impact on the performance of all-solid-state batteries. Currently, the manufacturing of positive electrode sheets for all-solid-state batteries is mainly divided into two categories: wet processes and dry processes. The wet process involves mixing the positive electrode active material, conductive agent, binder, and solvent to form a slurry, which is then coated onto the surface of the current collector and dried and compacted. This process suffers from high energy consumption, high solvent recovery costs, and environmental pollution; furthermore, the binder coats the surface of the active material, increasing the tortuosity of the ion transport path and hindering charge transport.
[0003] Dry processing eliminates the need for solvents, directly mixing active materials, binders, and conductive agents into powder, then using high-speed mechanical shearing force to draw and fibrillate them, roll them, or press them to form self-supporting electrodes. This method offers advantages such as low energy consumption and no solvent residue, making it a key research focus in the industry. Current dry processing typically uses polytetrafluoroethylene (PTFE) as a binder. Under pressure and shear force, PTFE forms a fibrous network structure to support the active material. However, this technology still has the following problems: First, the PTFE binder content needs to reach at least 2% to form a self-supporting film, but a high binder content hinders ion transport, and PTFE's high-pressure stability is insufficient; its degradation consumes active lithium. Second, in all-solid-state batteries, the contact between the cathode material particles and the solid electrolyte particles is rigid, easily forming fragile point-to-point contacts, resulting in high interfacial impedance, restricting electrode dynamics and capacity, and leading to cycle life degradation. Third, the positive electrode active material repeatedly expands and contracts in volume during charging and discharging. Unlike fluid liquid electrolytes, solid electrolytes struggle to adapt to this strain, easily leading to solid-solid interface detachment, void formation, increased interfacial impedance, and capacity decay. To maintain interfacial contact, current technologies typically require applying external pressures of tens or even hundreds of megapascals, but this introduces problems such as system complexity, reduced energy density, and mechanical fatigue. Fourth, conductive agents and binders, as inactive materials, reduce the proportion of active materials, limiting further improvements in battery energy density.
[0004] To address these issues, researchers have attempted to reduce the binder content or use materials that combine conductivity and adhesion. For example, one patent controls the binder content to below 5% by adding a conductive crosslinking polymer; another approach utilizes porous metal current collectors to fix the positive electrode material and solid electrolyte, thus eliminating dependence on binders. However, these approaches either still require the use of conductive agents and binders or rely on specific current collector structures, failing to fundamentally solve the aforementioned problems.
[0005] Therefore, there is an urgent need for a novel method for preparing composite cathode sheets for all-solid-state batteries that can achieve sufficient contact between particles without the use of conductive agents and binders, suppress interfacial failures during charge and discharge, and further improve the energy density and cycle stability of the battery. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a composite positive electrode sheet for all-solid-state batteries and its preparation method. The technical problem this invention aims to solve is: how to form a self-supporting composite positive electrode sheet by utilizing the ductile deformation of metal particles through a ternary mixed system of positive electrode material particles, metal particles, and solid electrolyte particles, without using conductive agents, binders, or current collectors. This solves the problems of high interfacial impedance between particles, easy interface detachment during charging and discharging, and limited energy density in existing all-solid-state battery positive electrode sheets.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solution: A composite positive electrode sheet for an all-solid-state battery, comprising, by weight percentage: The cathode material particles comprise 30% to 50%, the metal particles comprise 20% to 60%, and the solid electrolyte particles comprise 10% to 30%.
[0008] Preferably, the cathode material particles are selected from one or more of lithium-ion battery cathode materials, sodium-ion battery cathode materials, and carbon-supported sulfur materials; the lithium-ion battery cathode materials include lithium nickel cobalt manganese oxide, lithium iron phosphate, and lithium manganese oxide; the sodium-ion battery cathode materials include sodium sulfide, sodium nickel iron manganese oxide, sodium iron phosphate, and sodium ferrocyanide.
[0009] The metal particles are selected from one or more of Al, Sn, In, Bi, Mg, Cu, Fe, Ni, Zn and Mn, or an alloy composed of two or more of these metal elements; preferably, the metal is Al.
[0010] Preferably, the solid electrolyte particles are selected from lithium-ion electrolyte materials or sodium-ion electrolyte materials; the lithium-ion electrolyte material includes Li6PS5Cl, and the sodium-ion electrolyte material includes Na3PS4.
[0011] The positive electrode material particles and the solid electrolyte particles are encapsulated by the metal particles. The composite positive electrode does not contain conductive agents or binders, nor does it contain current collectors. The composite positive electrode has a self-supporting membrane structure.
[0012] The thickness of the composite positive electrode is 5μm~100μm, and the four-probe electronic conductivity is ≥17 S / cm.
[0013] Preferably, the electronic conductivity of the four probes is measured using the four probe method at 25°C.
[0014] A method for preparing a composite positive electrode sheet for an all-solid-state battery, comprising the following steps: S1. Provides cathode material particles, metal particles, and solid electrolyte particles; S2. Without adding liquid solvents, conductive agents, and polymer binders, the raw materials of the positive electrode material particles, the metal particles, and the solid electrolyte particles are dry-mixed to obtain a mixture; S3. The mixture is laid out as a layer to be compressed, and the layer to be compressed is subjected to tableting to obtain a tablet blank; S4. The tablet blank is subjected to heat treatment until the tablet blank reaches the preset hot pressing temperature to obtain a heat-treated tablet; S5. At the preset hot-pressing temperature, the heat-treated sheet is subjected to hot rolling at least twice, causing the metal particles to undergo ductile deformation, flow and spread to cover the surfaces of the positive electrode particles and electrolyte particles, connecting the three originally discrete particles into a continuous integrated film, thus obtaining a composite positive electrode sheet for all-solid-state batteries.
[0015] Preferably, the temperature of the heat treatment is 50℃~300℃; and the pressure of the hot roll calendering is 10MPa~1000MPa.
[0016] This invention provides a composite positive electrode sheet for all-solid-state batteries and its preparation method. It has the following beneficial effects: (1) A composite positive electrode sheet for all-solid-state batteries and its preparation method: By sequentially dry mixing, pressing, heat treatment, and two or more passes of roller calendering of positive electrode material particles, metal particles, and solid electrolyte particles, the metal particles undergo ductile flow deformation and interconnection under conditions without liquid solvent, conductive agent, and polymer binder, forming a continuous metal network that simultaneously encapsulates all positive electrode material particles and solid electrolyte particles, thus obtaining a self-supporting composite positive electrode sheet. This method eliminates the solvent treatment step and the use of polymer binders, simplifies the process, and reduces production costs.
[0017] (2) A ternary hybrid system of positive electrode material particles, metal particles, and solid electrolyte particles is adopted. Under the action of preset hot pressing temperature and rolling, the metal particles undergo ductile flow deformation, and the metal particles are interconnected to form a continuous metal network. The positive electrode material particles and solid electrolyte particles are simultaneously wrapped in the metal network. The metal network plays three roles: first, as an electron transport channel, it replaces the function of traditional conductive agents; second, as a structural support skeleton, it locks the particles together, replacing the function of traditional polymer binders; third, as an internal current collector, it realizes a self-supporting structure without the need for additional current collectors. By introducing a metal component, the functions of conductive agents, binders, and current collectors are simultaneously replaced, which greatly reduces the proportion of inactive materials and improves the energy density of the battery.
[0018] (3) The ductility of the metal particles allows them to tightly encapsulate the cathode material particles and solid electrolyte particles throughout the charging and discharging process. During the insertion and extraction of metal ions, the cathode material particles undergo periodic changes in their lattice parameters—the lattice contracts and the particle volume decreases during charging, while the lattice expands and the particle volume increases during discharging. The metal coating, due to its own ductility, can adaptively deform with the volume changes of the particles; the metal shell contracts when the particles contract and stretches when the particles expand, maintaining a tight encapsulation of the particle surface. This mechanism fundamentally avoids the problem of microcracks or detachment at traditional rigid solid-solid contact interfaces during volume changes, protecting interface integrity, suppressing the increase in interface impedance, and thus significantly improving the cycle stability of the battery. Simultaneously, because the metal coating itself can maintain interface contact, the battery does not require external pressure during use.
[0019] (4) The metal network itself has excellent electronic conductivity, so the composite positive electrode does not require an additional current collector; at the same time, since no conductive agent and binder are used, the proportion of inactive material is reduced and the proportion of active material is increased, thereby improving the energy density of the battery. The composite positive electrode has ductility, adjustable thickness, excellent processing performance, simple process, and low equipment investment.
[0020] (5) The metal network encapsulates the cathode material particles and solid electrolyte particles into an integrated membrane structure. Unlike the point contact or limited surface contact between particles in traditional dry-process electrodes, which is maintained only by a PTFE fiber network, the cathode material particles and solid electrolyte particles in this invention are in direct contact or indirectly contacted through a metal layer, significantly reducing the interface impedance. The alloy coating layer can suppress the volume shrinkage and expansion of particles caused by charging and discharging, resulting in good battery cycle performance. Attached Figure Description
[0021] Figure 1 This is a process flow diagram for the preparation of the composite positive electrode sheet of the all-solid-state battery of the present invention; Figure 2 This is a schematic cross-sectional view of the composite positive electrode sheet prepared in Embodiment 1 of the present invention; Figure 3 This is a charge-discharge curve diagram of the Al-S / C / Li6PS5Cl / Li battery in Embodiment 5 of the present invention, where the upper curve is the charging curve and the lower curve is the discharging curve. Figure 4 This is a charge-discharge curve diagram of the Al-NCM / Li6PS5Cl / Li battery in Embodiment 7 of the present invention for the first cycle, where the upper curve is the charging curve and the lower curve is the discharging curve. Detailed Implementation
[0022] The technical solutions in the embodiments of the present invention have been clearly and completely described. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] Example 1 like Figures 1-2 As shown, this embodiment of the invention provides a composite positive electrode sheet for an all-solid-state battery and its preparation method, including the following steps: S1. By mass percentage, the product comprises 30%–50% positive electrode material particles, 20%–60% metal particles, and 10%–30% solid electrolyte particles. The positive electrode material particles are selected from one or more of lithium-ion battery positive electrode materials, sodium-ion battery positive electrode materials, and carbon-supported sulfur materials. Lithium-ion battery positive electrode materials include lithium nickel cobalt manganese oxide, lithium iron phosphate, and lithium manganese oxide; sodium-ion battery positive electrode materials include sodium sulfide, sodium nickel iron manganese oxide, sodium iron phosphate, and sodium ferrocyanate. The metal particles are selected from one or more of Al, Sn, In, Bi, Mg, Cu, Fe, Ni, Zn, and Mn, or alloys composed of two or more of these metal elements. The solid electrolyte particles are selected from lithium-ion battery electrolyte materials or sodium-ion battery electrolyte materials; the lithium-ion battery electrolyte material is Li6PS5Cl, and the sodium-ion battery electrolyte material is Na3PS4.
[0024] S2. Without adding liquid solvents, conductive agents, and polymer binders, the raw materials of positive electrode material particles, metal particles, and solid electrolyte particles are dry-mixed to obtain a mixture.
[0025] S3. The mixture is laid out as the material to be compressed, and the material to be compressed is subjected to tableting treatment. The three types of particles are initially aggregated and compacted, and an initial contact interface is established between the particles to obtain a tablet blank that can be independently demolded. No positive electrode current collector is set during the tableting process, and the resulting tablet blank is an independent blank.
[0026] S4. Heat-treat the tablet blank until it reaches the preset hot-pressing temperature of 50℃~300℃ to obtain a heat-treated tablet.
[0027] S5. Under the conditions of preset hot pressing temperature and pressure of 10MPa~1000MPa, the heat-treated sheet is subjected to hot rolling at least twice. The metal particles undergo ductile deformation, flow and spread to cover the surface of the positive electrode particles and electrolyte particles, connecting the three originally discrete particles into a continuous integrated film, thus producing a self-supporting composite positive electrode sheet for all-solid-state batteries.
[0028] The compression process establishes initial particle contact points between the cathode material particles, metal particles, and solid electrolyte particles. Heat treatment brings the compressed sheet to a hot-pressing temperature compatible with the metal particles. Two or more passes of hot rolling induce ductile flow deformation in the metal particles, causing them to interconnect and form a continuous metal network. This network simultaneously encapsulates the cathode material and solid electrolyte particles, embedding them within the metal layer. The continuous metal network serves to connect adjacent cathode material and solid electrolyte particles and support the sheet structure, allowing the electrode to form a continuous, self-supporting film without the need for a polymer binder fiber network. Multiple passes of hot rolling also allow for gradual adjustment of the sheet thickness, resulting in a stable structure for the composite cathode electrode.
[0029] The metal network serves three functions simultaneously: first, as an electron transport channel, replacing traditional conductive agents; second, as a structural support framework, replacing traditional polymer binders; and third, as an internal current collector, eliminating the need for an additional current collector. Multiple metal particles collectively form a continuous metal network, embedding the positive electrode material particles and solid electrolyte particles within it. The metal network enables inter-particle connectivity and supports the sheet structure. Multi-pass rolling further allows for gradual adjustment of the sheet thickness, resulting in a stable, self-supporting membrane structure for the composite positive electrode sheet.
[0030] Example 2 The embodiments of the present invention are used to illustrate the implementation of preparing a sodium-sulfur all-solid-state battery composite cathode sheet using Al metal particles, carbon-supported sulfur cathode material particles and Na3PS4 solid electrolyte particles, and assembling a sodium-sulfur all-solid-state battery.
[0031] 1. Preparation of composite positive electrode sheet Weigh the raw materials according to the following percentages by mass: 45% Al metal particles, 35% carbon-supported sulfur cathode material particles, and 20% Na3PS4 solid electrolyte particles, for a total mass of 100g.
[0032] Without adding liquid solvents, conductive agents, or polymer binders, Al metal particles, carbon-supported sulfur cathode material particles, and Na3PS4 solid electrolyte particles were dry-mixed at 300 r / min for 30 min to obtain a mixture.
[0033] The mixture is laid as the material to be compressed and pre-compressed at 20MPa for 60s to obtain a tablet blank that can be demolded independently.
[0034] The tablet blank is heated to a preset hot-pressing temperature of 80°C and held for 10 minutes. Then, the blank is calendered in three passes using a roller press with a roller speed of 0.5 m / min. The roller gaps for the three passes are 120 μm, 80 μm and 50 μm respectively. The hydraulic loading system is set to a pressure of 100 MPa and the roller surface temperature is maintained at 80°C.
[0035] During the hot roll forming process, Al metal particles undergo ductile flow deformation, and the Al metal particles connect with each other to form a continuous metal network, which simultaneously encapsulates all the carbon-supported sulfur cathode material particles and Na3PS4 solid electrolyte particles.
[0036] After calendering, a composite positive electrode sheet with a thickness of 50 μm is obtained, which does not contain conductive agent, binder and current collector.
[0037] 2. Electrode performance testing The electronic conductivity of the self-supporting positive electrode was measured using the four-probe method, and the result was 35.8 S / cm.
[0038] 3. Preparation of solid electrolyte membranes Na3PS4 solid electrolyte and polytetrafluoroethylene (PTFE) were dry-mixed at a mass ratio of 98:2 and pressed into a membrane at 80℃ and 100MPa to obtain a solid electrolyte membrane with a thickness of 80μm.
[0039] 4. Battery assembly and electrochemical testing The self-supporting composite positive electrode sheet was cut into 20mm×20mm pieces and laminated with a Na3PS4 solid electrolyte membrane. A sodium metal negative electrode was then added to complete the assembly of the small pouch cell. An external pressure of 0.1MPa was applied to the resulting cell using a fixture.
[0040] The battery was tested for charge and discharge at 25°C, with a voltage range of 0.3V to 2.8V and a charge and discharge current of 350μA.
[0041] Test results show that the charging capacity in the first cycle is 634 mAh / g, the discharging capacity is 710 mAh / g, and the coulombic efficiency in the first cycle is 112%. After 50 cycles, the charging capacity is 642 mAh / g, the discharging capacity is 675 mAh / g, the coulombic efficiency in the 50th cycle is 105%, and the cycle maintenance rate is 95%.
[0042] Test results show that the composite cathode sheet prepared by Al metal particles, carbon-supported sulfur cathode material particles, and Na3PS4 solid electrolyte particles can be used in sodium-sulfur all-solid-state batteries and has good cycle stability.
[0043] Example 3 The embodiments of the present invention are used to illustrate the implementation of preparing a sodium-sulfur all-solid-state battery composite cathode sheet using Al metal particles, carbon-supported sulfur cathode material particles and Na3PS4 solid electrolyte particles, and assembling a sodium-sulfur all-solid-state battery.
[0044] 1. Preparation of composite positive electrode sheet Weigh the raw materials according to the following percentages by mass: 20% Al metal particles, 50% carbon-supported sulfur cathode material particles, and 30% Na3PS4 solid electrolyte particles, for a total mass of 100g.
[0045] Without adding liquid solvents, conductive agents, or polymer binders, Al metal particles, carbon-supported sulfur cathode material particles, and Na3PS4 solid electrolyte particles were dry-mixed at 300 r / min for 30 min to obtain a mixture.
[0046] The mixture is laid out as the material to be compressed and pre-compressed at 10MPa for 60s to obtain a tablet blank that can be demolded independently.
[0047] The tablet blank is heated to a preset hot-pressing temperature of 80°C and held for 10 minutes. Then, the blank is calendered in three passes using a roller press with a roller speed of 0.5 m / min. The roller gaps for the three passes are 120 μm, 80 μm and 50 μm respectively. The hydraulic loading system is set to a pressure of 100 MPa and the roller surface temperature is maintained at 80°C.
[0048] After calendering, a composite positive electrode sheet with a thickness of 50 μm is obtained without a positive current collector.
[0049] 2. Electrode performance testing The electronic conductivity of the self-supporting positive electrode was measured using the four-probe method, and the result was 17.3 S / cm.
[0050] 3. Preparation of solid electrolyte membranes Na3PS4 solid electrolyte and PTFE were dry-mixed at a mass ratio of 98:2 and pressed into a membrane at 80℃ and 100MPa to obtain a solid electrolyte membrane with a thickness of 80μm.
[0051] 4. Battery assembly and electrochemical testing The self-supporting composite positive electrode sheet was cut into 20mm×20mm pieces and laminated with a Na3PS4 solid electrolyte membrane. A sodium metal negative electrode was then added to complete the assembly of the small pouch cell. An external pressure of 0.1MPa was applied to the resulting cell using a fixture.
[0052] The battery was tested for charge and discharge at 25°C, with a voltage range of 0.3V to 2.8V and a charge and discharge current of 350μA.
[0053] Test results show that the charging capacity in the first cycle is 558 mAh / g, the discharging capacity is 697 mAh / g, and the coulombic efficiency in the first cycle is 125%. After 50 cycles, the charging capacity is 574 mAh / g, the discharging capacity is 614 mAh / g, the coulombic efficiency in the 50th cycle is 107%, and the cycle maintenance rate is 88%.
[0054] Test results show that the composite cathode sheet prepared by Al metal particles, carbon-supported sulfur cathode material particles, and Na3PS4 solid electrolyte particles can be used in sodium-sulfur all-solid-state batteries and has good cycle stability.
[0055] Example 4 The embodiments of the present invention are used to illustrate the implementation of preparing a sodium-sulfur all-solid-state battery composite cathode sheet using Al metal particles, carbon-supported sulfur cathode material particles and Na3PS4 solid electrolyte particles, and assembling a sodium-sulfur all-solid-state battery.
[0056] 1. Preparation of composite positive electrode sheet Weigh the raw materials according to the following percentages by mass: 60% Al metal particles, 30% carbon-supported sulfur cathode material particles, and 10% Na3PS4 solid electrolyte particles, for a total mass of 100g.
[0057] Without adding liquid solvents, conductive agents, or polymer binders, Al metal particles, carbon-supported sulfur cathode material particles, and Na3PS4 solid electrolyte particles were dry-mixed at 300 r / min for 30 min to obtain a mixture.
[0058] The mixture is laid out as the material to be compressed and pre-compressed at 100MPa for 60s to obtain a tablet blank that can be demolded independently.
[0059] The tablet blank is heated to a preset hot-pressing temperature of 80°C and held for 10 minutes. Then, the blank is calendered in three passes using a roller press with a roller speed of 0.5 m / min. The roller gaps for the three passes are 120 μm, 80 μm and 50 μm respectively. The hydraulic loading system is set to a pressure of 100 MPa and the roller surface temperature is maintained at 80°C.
[0060] After calendering, a composite positive electrode sheet with a thickness of 50 μm is obtained, which does not contain conductive agent, binder and current collector.
[0061] 2. Electrode performance testing The electronic conductivity of the self-supporting positive electrode was measured using the four-probe method, and the result was 44.1 S / cm.
[0062] 3. Preparation of solid electrolyte membranes Na3PS4 solid electrolyte and PTFE were dry-mixed at a mass ratio of 98:2 and pressed into a membrane at 80℃ and 100MPa to obtain a solid electrolyte membrane with a thickness of 80μm.
[0063] 4. Battery assembly and electrochemical testing The self-supporting composite positive electrode sheet was cut into 20mm×20mm pieces and laminated with a Na3PS4 solid electrolyte membrane. A sodium metal negative electrode was then added to complete the assembly of the small pouch cell. An external pressure of 0.1MPa was applied to the resulting cell using a fixture.
[0064] The battery was tested for charge and discharge at 25°C, with a voltage range of 0.3V to 2.8V and a charge and discharge current of 350μA.
[0065] Test results show that the charging capacity in the first cycle is 609 mAh / g, the discharging capacity is 834 mAh / g, and the coulombic efficiency in the first cycle is 137%. After 50 cycles, the charging capacity is 757 mAh / g, the discharging capacity is 825 mAh / g, the coulombic efficiency in the 50th cycle is 109%, and the cycle maintenance rate is 99%.
[0066] Test results show that the composite cathode sheet prepared by Al metal particles, carbon-supported sulfur cathode material particles, and Na3PS4 solid electrolyte particles can be used in sodium-sulfur all-solid-state batteries and has good cycle stability.
[0067] Example 5 The embodiments of the present invention are used to illustrate the implementation of preparing a composite cathode sheet for a lithium-sulfur all-solid-state battery using Al metal particles, carbon-supported sulfur cathode material particles and Li6PS5Cl solid electrolyte particles, and assembling a lithium-sulfur all-solid-state battery.
[0068] 1. Preparation of composite positive electrode sheet Weigh the raw materials according to the following percentages by mass: 60% Al metal particles, 30% carbon-supported sulfur cathode material particles, and 10% Li6PS5Cl solid electrolyte particles, for a total mass of 100g.
[0069] Without adding liquid solvents, conductive agents, or polymer binders, Al metal particles, carbon-supported sulfur cathode material particles, and Li6PS5Cl solid electrolyte particles were dry-mixed at 300 r / min for 30 min to obtain a mixture.
[0070] The mixture is laid out as the material to be compressed and pre-compressed at 100MPa for 60s to obtain a tablet blank that can be demolded independently.
[0071] The tablet blank is heated to a preset hot-pressing temperature of 80°C and held for 10 minutes. Then, the blank is calendered in three passes using a roller press with a roller speed of 0.5 m / min. The roller gaps for the three passes are 120 μm, 80 μm and 50 μm respectively. The hydraulic loading system is set to a pressure of 100 MPa and the roller surface temperature is maintained at 80°C.
[0072] After calendering, a composite positive electrode sheet with a thickness of 50 μm is obtained, which does not contain conductive agent, binder and current collector.
[0073] 2. Electrode performance testing The electronic conductivity of the self-supporting positive electrode was measured using the four-probe method, and the result was 45.8 S / cm.
[0074] 3. Preparation of solid electrolyte membranes Li6PS5Cl solid electrolyte and PTFE were dry-mixed at a mass ratio of 98:2 and pressed into a membrane at 80℃ and 100MPa to obtain a solid electrolyte membrane with a thickness of 80μm.
[0075] 4. Battery assembly and electrochemical testing The self-supporting composite positive electrode sheet was cut into 20mm×20mm pieces and laminated with a Li6PS5Cl solid electrolyte membrane. A lithium metal negative electrode was then added to complete the assembly of the small pouch cell. An external pressure of 0.1MPa was applied to the resulting cell using a fixture.
[0076] The battery was tested for charge and discharge at 25°C, with a voltage range of 0.3V to 2.8V and a charge and discharge current of 350μA.
[0077] Test results show that the charging capacity in the first cycle is 577 mAh / g, the discharging capacity is 738 mAh / g, and the coulombic efficiency in the first cycle is 128%. After 50 cycles, the charging capacity is 724 mAh / g, the discharging capacity is 746 mAh / g, the coulombic efficiency in the 50th cycle is 103%, and the cycle maintenance rate is 101%.
[0078] Figure 3 This is the first charge-discharge curve of the Al-S / C / Li6PS5Cl / Li battery in this embodiment.
[0079] Test results show that the composite cathode sheet prepared by Al metal particles, carbon-supported sulfur cathode material particles, and Li6PS5Cl solid electrolyte particles can be used in lithium-sulfur all-solid-state batteries and has good cycle stability.
[0080] Example 6 The embodiments of the present invention are used to illustrate the implementation of preparing a sodium-ion all-solid-state battery composite positive electrode sheet using Al metal particles, sodium nickel iron manganese oxide positive electrode material particles and Na3PS4 solid electrolyte particles, and assembling a sodium-ion all-solid-state battery.
[0081] 1. Preparation of composite positive electrode sheet NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is used as the sodium nickel iron manganese oxide cathode material (hereinafter referred to as NNFM). The raw materials are weighed according to the following mass percentages: 60% Al metal particles, 30% NNFM cathode material particles, and 10% Na3PS4 solid electrolyte particles, with a total mass of 100g.
[0082] Without adding liquid solvents, conductive agents, or polymer binders, Al metal particles, NNFM cathode material particles, and Na3PS4 solid electrolyte particles were dry-mixed at 300 r / min for 30 min to obtain a mixture.
[0083] The mixture is laid out as the material to be compressed and pre-compressed at 100MPa for 60s to obtain a tablet blank that can be demolded independently.
[0084] The tablet blank is heated to a preset hot-pressing temperature of 80°C and held for 10 minutes. Then, the blank is calendered in three passes using a roller press with a roller speed of 0.5 m / min. The roller gaps for the three passes are 120 μm, 80 μm and 50 μm respectively. The hydraulic loading system is set to a pressure of 100 MPa and the roller surface temperature is maintained at 80°C.
[0085] After calendering, a composite positive electrode sheet with a thickness of 50 μm is obtained, which does not contain conductive agent, binder and current collector.
[0086] 2. Electrode performance testing The electronic conductivity of the self-supporting positive electrode was measured using the four-probe method, and the result was 23.6 S / cm.
[0087] 3. Preparation of solid electrolyte membranes Na3PS4 solid electrolyte and PTFE were dry-mixed at a mass ratio of 98:2 and pressed into a membrane at 80℃ and 100MPa to obtain a solid electrolyte membrane with a thickness of 80μm.
[0088] 4. Battery assembly and electrochemical testing The self-supporting composite positive electrode sheet was cut into 20mm×20mm pieces and laminated with a Na3PS4 solid electrolyte membrane. A sodium metal negative electrode was then added to complete the assembly of the small pouch cell. An external pressure of 0.1MPa was applied to the resulting cell using a fixture.
[0089] The battery was tested for charge and discharge at 25°C, with a voltage range of 2.0V to 3.8V and a charge and discharge current of 350μA.
[0090] Test results show that the charging capacity in the first cycle is 138 mAh / g, the discharging capacity is 131 mAh / g, and the coulombic efficiency in the first cycle is 95%. After 50 cycles, the charging capacity is 120 mAh / g, the discharging capacity is 117 mAh / g, the coulombic efficiency in the 50th cycle is 97%, and the cycle maintenance rate is 89%.
[0091] Test results show that the composite cathode sheet prepared by Al metal particles, NNFM cathode material particles and Na3PS4 solid electrolyte particles can be used in sodium-ion all-solid-state batteries and has good cycle stability.
[0092] Example 7 The embodiments of the present invention are used to illustrate the implementation of preparing a composite positive electrode sheet for a lithium-ion all-solid-state battery using Al metal particles, high-nickel ternary cathode material particles and Li6PS5Cl solid electrolyte particles, and assembling a lithium-ion all-solid-state battery.
[0093] 1. Preparation of composite positive electrode sheet Using LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) is used as a high-nickel ternary cathode material. The raw materials are weighed according to the following mass percentages: 60% Al metal particles, 30% high-nickel ternary cathode material particles, and 10% Li6PS5Cl solid electrolyte particles, with a total mass of 100g.
[0094] Without adding liquid solvents, conductive agents, or polymer binders, Al metal particles, high-nickel ternary cathode material particles, and Li6PS5Cl solid electrolyte particles were dry-mixed at 300 r / min for 30 min to obtain a mixture.
[0095] The mixture is laid out as the material to be compressed and pre-compressed at 100MPa for 60s to obtain a tablet blank that can be demolded independently.
[0096] The tablet blank is heated to a preset hot-pressing temperature of 80°C and held for 10 minutes. Then, the blank is calendered in three passes using a roller press with a roller speed of 0.5 m / min. The roller gaps for the three passes are 120 μm, 80 μm and 50 μm respectively. The hydraulic loading system is set to a pressure of 100 MPa and the roller surface temperature is maintained at 80°C.
[0097] After calendering, a composite positive electrode sheet with a thickness of 50 μm is obtained, which does not contain conductive agent, binder and current collector.
[0098] 2. Electrode performance testing The electronic conductivity of the self-supporting positive electrode was measured using the four-probe method, and the result was 27.2 S / cm.
[0099] 3. Preparation of solid electrolyte membranes Li6PS5Cl solid electrolyte and PTFE were dry-mixed at a mass ratio of 98:2 and pressed into a membrane at 80℃ and 100MPa to obtain a solid electrolyte membrane with a thickness of 80μm.
[0100] 4. Battery assembly and electrochemical testing The self-supporting composite positive electrode sheet was cut into 20mm×20mm pieces and laminated with a Li6PS5Cl solid electrolyte membrane. A lithium metal negative electrode was then added to complete the assembly of the small pouch cell. An external pressure of 0.1MPa was applied to the resulting cell using a fixture.
[0101] The battery was tested for charge and discharge at 25°C, with a voltage range of 3.0V to 4.2V and a charge and discharge current of 350μA.
[0102] Test results show that the charging capacity in the first cycle is 177 mAh / g, the discharging capacity is 159 mAh / g, and the coulombic efficiency in the first cycle is 90%. After 50 cycles, the charging capacity is 143 mAh / g, the discharging capacity is 137 mAh / g, the coulombic efficiency in the 50th cycle is 96%, and the cycle maintenance rate is 86%.
[0103] Figure 4 This is the first charge-discharge curve of the Al-NCM / Li6PS5Cl / Li battery in this embodiment.
[0104] Test results show that the composite cathode sheet prepared by Al metal particles, high-nickel ternary cathode material particles, and Li6PS5Cl solid electrolyte particles can be used in lithium-ion all-solid-state batteries and has good cycle stability.
[0105] Example 8 The embodiments of the present invention are used to illustrate the implementation of preparing a composite positive electrode sheet for a lithium-ion all-solid-state battery using Al metal particles, lithium iron phosphate positive electrode material particles and Li6PS5Cl solid electrolyte particles, and assembling a lithium-ion all-solid-state battery.
[0106] 1. Preparation of composite positive electrode sheet LiFePO4 was used as the lithium iron phosphate cathode material. The raw materials were weighed according to the following mass percentages: 60% Al metal particles, 30% lithium iron phosphate cathode material particles, and 10% Li6PS5Cl solid electrolyte particles, for a total mass of 100g.
[0107] Without adding liquid solvents, conductive agents, or polymer binders, Al metal particles, lithium iron phosphate cathode material particles, and Li6PS5Cl solid electrolyte particles were dry-mixed at 300 r / min for 30 min to obtain a mixture.
[0108] The mixture is laid out as the material to be compressed and pre-compressed at 100MPa for 60s to obtain a tablet blank that can be demolded independently.
[0109] The tablet blank is heated to a preset hot-pressing temperature of 80°C and held for 10 minutes. Then, the blank is calendered in three passes using a roller press with a roller speed of 0.5 m / min. The roller gaps for the three passes are 120 μm, 80 μm and 50 μm respectively. The hydraulic loading system is set to a pressure of 100 MPa and the roller surface temperature is maintained at 80°C.
[0110] After calendering, a composite positive electrode sheet with a thickness of 50 μm is obtained, which does not contain conductive agent, binder and current collector.
[0111] 2. Electrode performance testing The electronic conductivity of the self-supporting positive electrode was measured using the four-probe method, and the result was 21.4 S / cm.
[0112] 3. Preparation of solid electrolyte membranes Li6PS5Cl solid electrolyte and PTFE were dry-mixed at a mass ratio of 98:2 and pressed into a membrane at 80℃ and 100MPa to obtain a solid electrolyte membrane with a thickness of 80μm.
[0113] 4. Battery assembly and electrochemical testing The self-supporting composite positive electrode sheet was cut into 20mm×20mm pieces and laminated with a Li6PS5Cl solid electrolyte membrane. A lithium metal negative electrode was then added to complete the assembly of the small pouch cell. An external pressure of 0.1MPa was applied to the resulting cell using a fixture.
[0114] The battery was tested for charge and discharge at 25°C, with a voltage range of 2.0V to 3.6V and a charge and discharge current of 350μA.
[0115] Test results show that the charging capacity in the first cycle is 129 mAh / g, the discharging capacity is 120 mAh / g, and the coulombic efficiency in the first cycle is 93%. After 50 cycles, the charging capacity is 114 mAh / g, the discharging capacity is 108 mAh / g, the coulombic efficiency in the 50th cycle is 95%, and the cycle maintenance rate is 90%.
[0116] Test results show that the composite cathode sheet prepared by Al metal particles, lithium iron phosphate cathode material particles and Li6PS5Cl solid electrolyte particles can be used in lithium-ion all-solid-state batteries and has good cycle stability.
[0117] Example 9 The embodiments of the present invention are used to illustrate the implementation of preparing a composite cathode sheet for a lithium-sulfur all-solid-state battery using Cu metal particles, carbon-supported sulfur cathode material particles, and Li6PS5Cl solid electrolyte particles, and assembling a lithium-sulfur all-solid-state battery.
[0118] 1. Preparation of composite positive electrode sheet Weigh the raw materials according to the following percentages by mass: 35% Cu metal particles, 40% carbon-supported sulfur cathode material particles, and 25% Li6PS5Cl solid electrolyte particles, for a total mass of 100g.
[0119] Without adding liquid solvents, conductive agents, or polymer binders, Cu metal particles, carbon-supported sulfur cathode material particles, and Li6PS5Cl solid electrolyte particles were dry-mixed at 300 r / min for 30 min to obtain a mixture.
[0120] The mixture is laid out as the material to be compressed and pre-compressed at 100MPa for 60s to obtain a tablet blank that can be demolded independently.
[0121] The tablet blank is heated to a preset hot-pressing temperature of 80°C and held for 10 minutes. Then, the blank is calendered in three passes using a roller press with a roller speed of 0.5 m / min. The roller gaps for the three passes are 120 μm, 80 μm and 50 μm respectively. The hydraulic loading system is set to a pressure of 100 MPa and the roller surface temperature is maintained at 80°C.
[0122] After calendering, a composite positive electrode sheet with a thickness of 50 μm is obtained, which does not contain conductive agent, binder and current collector.
[0123] 2. Electrode performance testing The electronic conductivity of the self-supporting positive electrode was measured using the four-probe method, and the result was 27.1 S / cm.
[0124] 3. Preparation of solid electrolyte membranes Li6PS5Cl solid electrolyte and PTFE were dry-mixed at a mass ratio of 98:2 and pressed into a membrane at 80℃ and 100MPa to obtain a solid electrolyte membrane with a thickness of 80μm.
[0125] 4. Battery assembly and electrochemical testing The self-supporting composite positive electrode sheet was cut into 20mm×20mm pieces and laminated with a Li6PS5Cl solid electrolyte membrane. A lithium metal negative electrode was then added to complete the assembly of the small pouch cell. An external pressure of 0.1MPa was applied to the resulting cell using a fixture.
[0126] The battery was tested for charge and discharge at 25°C, with a voltage range of 0.3V to 2.8V and a charge and discharge current of 350μA.
[0127] Test results show that the charging capacity in the first cycle is 653 mAh / g, the discharging capacity is 758 mAh / g, and the coulombic efficiency in the first cycle is 116%. After 50 cycles, the charging capacity is 678 mAh / g, the discharging capacity is 712 mAh / g, the coulombic efficiency in the 50th cycle is 105%, and the cycle maintenance rate is 94%.
[0128] Test results show that the composite cathode sheet prepared by Cu metal particles, carbon-supported sulfur cathode material particles, and Li6PS5Cl solid electrolyte particles can be used in lithium-sulfur all-solid-state batteries and has good cycle stability.
[0129] Example 10 The embodiments of the present invention are used to illustrate the implementation of preparing a composite cathode sheet for a lithium-sulfur all-solid-state battery using InSnBi alloy particles, carbon-supported sulfur cathode material particles and Li6PS5Cl solid electrolyte particles, and assembling a lithium-sulfur all-solid-state battery.
[0130] 1. Preparation of composite positive electrode sheet The raw materials are weighed according to the following mass percentages: 35% InSnBi alloy particles, 40% carbon-supported sulfur cathode material particles, and 25% Li6PS5Cl solid electrolyte particles, with a total mass of 100g. The molar ratio of In, Sn, and Bi in the InSnBi alloy is 1:1:1.
[0131] Without adding liquid solvents, conductive agents, or polymer binders, InSnBi alloy particles, carbon-supported sulfur cathode material particles, and Li6PS5Cl solid electrolyte particles were dry-mixed at 300 r / min for 30 min to obtain a mixture.
[0132] The mixture is laid out as the material to be compressed and pre-compressed at 100MPa for 60s to obtain a tablet blank that can be demolded independently.
[0133] The tablet blank is heated to a preset hot-pressing temperature of 80°C and held for 10 minutes. Then, the blank is calendered in three passes using a roller press with a roller speed of 0.5 m / min. The roller gaps for the three passes are 120 μm, 80 μm and 50 μm respectively. The hydraulic loading system is set to a pressure of 100 MPa and the roller surface temperature is maintained at 80°C.
[0134] After calendering, a composite positive electrode sheet with a thickness of 50 μm is obtained, which does not contain conductive agent, binder and current collector.
[0135] 2. Electrode performance testing The electronic conductivity of the self-supporting positive electrode was measured using the four-probe method, and the result was 25.5 S / cm.
[0136] 3. Preparation of solid electrolyte membranes Li6PS5Cl solid electrolyte and PTFE were dry-mixed at a mass ratio of 98:2 and pressed into a membrane at 80℃ and 100MPa to obtain a solid electrolyte membrane with a thickness of 80μm.
[0137] 4. Battery assembly and electrochemical testing The self-supporting composite positive electrode sheet was cut into 20mm×20mm pieces and laminated with a Li6PS5Cl solid electrolyte membrane. A lithium metal negative electrode was then added to complete the assembly of the small pouch cell. An external pressure of 0.1MPa was applied to the resulting cell using a fixture.
[0138] The battery was tested for charge and discharge at 25°C, with a voltage range of 0.3V to 2.8V and a charge and discharge current of 350μA.
[0139] Test results show that the charging capacity in the first cycle is 590mAh / g, the discharging capacity is 802mAh / g, and the coulombic efficiency in the first cycle is 136%. After 50 cycles, the charging capacity is 646mAh / g, the discharging capacity is 730mAh / g, the coulombic efficiency in the 50th cycle is 113%, and the cycle maintenance rate is 91%.
[0140] Test results show that the composite cathode sheet prepared by InSnBi alloy particles, carbon-supported sulfur cathode material particles, and Li6PS5Cl solid electrolyte particles can be used in lithium-sulfur all-solid-state batteries and has good cycle stability.
[0141] Comparative Example 1 This comparative example illustrates an implementation method for preparing carbon-supported sulfur cathode films using a conventional dry process employing conductive carbon and polymer binders, and is compared with Example 5.
[0142] 1. Preparation of positive electrode film The positive electrode membrane was prepared in an argon-protected environment where the water and oxygen content were both below 1 ppm.
[0143] The carbon-supported sulfur cathode material, Li6PS5Cl solid electrolyte, conductive carbon, and polymer binder were weighed according to a mass ratio of 70:25:2:3. The polymer binder was PTFE.
[0144] The raw materials were dry-mixed at 300 r / min for 30 min and sheared at 60℃ for 20 min to form a fibrous bonded network of PTFE.
[0145] The mixture was subjected to three dry calendering processes at 80℃ and 100MPa to obtain a positive electrode film with an average thickness of 50μm.
[0146] 2. Electrode performance testing The electronic conductivity of the obtained positive electrode film was detected using the four-probe method, and the result was 5.6 S / cm.
[0147] 3. Preparation of solid electrolyte membranes Li6PS5Cl solid electrolyte and PTFE were dry-mixed at a mass ratio of 98:2 and pressed into a membrane at 80℃ and 100MPa to obtain a solid electrolyte membrane with a thickness of 80μm.
[0148] 4. Battery assembly and electrochemical testing The positive electrode membrane was cut to 20mm × 20mm and stacked with a Li6PS5Cl solid electrolyte membrane. A lithium metal negative electrode was then added to complete the assembly of the small pouch cell. An external pressure of 0.1MPa was applied to the resulting cell using a fixture.
[0149] The battery was tested for charge and discharge at 25°C, with a voltage range of 0.3V to 2.8V and a charge and discharge current of 350μA.
[0150] Test results show that the charging capacity in the first cycle is 490mAh / g, the discharging capacity is 613mAh / g, and the coulombic efficiency in the first cycle is 125%. After 50 cycles, the charging capacity is 494mAh / g, the discharging capacity is 509mAh / g, the coulombic efficiency in the 50th cycle is 103%, and the cycle maintenance rate is 83%.
[0151] Example 5 and Comparative Example 1 used the same positive electrode active material and solid electrolyte. The difference between the two is that Example 5 uses Al metal particles instead of conductive agents and binders, and includes solid electrolyte particles. A self-supporting composite positive electrode sheet is formed by the ductile deformation of the Al metal particles without the addition of conductive agents and binders. Comparative Example 1, on the other hand, relies on a conductive carbon and polytetrafluoroethylene fibrous bonding network to form the positive electrode film. The in-plane electronic conductivity of the electrode sheet in Example 5 is 45.8 S / cm, which is much higher than the 5.6 S / cm of Comparative Example 1. Furthermore, the cycle retention rate after 50 cycles is 101%, which is also higher than the 83% of Comparative Example 1.
[0152] Comparative Example 2 This comparative example illustrates an implementation method for preparing NNFM cathode films using a conventional dry process employing conductive carbon and polymer binders, and is compared with Example Six.
[0153] 1. Preparation of positive electrode film The positive electrode membrane was prepared in an argon-protected environment where the water and oxygen content were both below 1 ppm.
[0154] NNFM was used as the positive electrode material. NNFM positive electrode material, Na3PS4 solid electrolyte, conductive carbon, and polymer binder were weighed according to a mass ratio of 70:25:2:3. The polymer binder was PTFE.
[0155] The raw materials were dry-mixed at 300 r / min for 30 min and sheared at 60℃ for 20 min to form a fibrous bonding network of polytetrafluoroethylene.
[0156] The mixture was subjected to three dry calendering processes at 80℃ and 100MPa to obtain a positive electrode film with an average thickness of 50μm.
[0157] 2. Electrode performance testing The electronic conductivity of the obtained positive electrode film was detected using the four-probe method, and the result was 0.78 S / cm.
[0158] 3. Preparation of solid electrolyte membranes Na3PS4 solid electrolyte and PTFE were dry-mixed at a mass ratio of 98:2 and pressed into a membrane at 80℃ and 100MPa to obtain a solid electrolyte membrane with a thickness of 80μm.
[0159] 4. Battery assembly and electrochemical testing The positive electrode membrane was cut to 20mm × 20mm and stacked with a Na3PS4 solid electrolyte membrane. A sodium metal negative electrode was then added to complete the assembly of the small pouch cell. An external pressure of 0.1MPa was applied to the resulting cell using a fixture.
[0160] The battery was tested for charge and discharge at 25°C, with a voltage range of 2.0V to 3.8V and a charge and discharge current of 350μA.
[0161] Test results show that the charging capacity in the first cycle is 131 mAh / g, the discharging capacity is 122 mAh / g, and the coulombic efficiency in the first cycle is 93%. After 50 cycles, the charging capacity is 110 mAh / g, the discharging capacity is 105 mAh / g, the coulombic efficiency in the 50th cycle is 95%, and the cycle maintenance rate is 86%.
[0162] Example 6 and Comparative Example 2 used the same positive electrode active material and solid electrolyte. The difference between the two is that Example 6 uses Al metal particles instead of conductive agents and binders, and includes solid electrolyte particles. A self-supporting composite positive electrode sheet is formed by the ductile deformation of the Al metal particles without the addition of conductive agents and binders. Comparative Example 2, on the other hand, relies on a conductive carbon and PTFE fibrous bonding network to form the positive electrode film. The in-plane electronic conductivity of the electrode sheet in Example 6 is 23.6 S / cm, which is much higher than the 0.78 S / cm of Comparative Example 2. Furthermore, the cycle retention rate after 50 cycles is 89%, which is higher than the 86% of Comparative Example 2.
[0163] Comparative Example 3 This comparative example illustrates an implementation method for preparing high-nickel ternary cathode films using a conventional dry process employing conductive carbon and polymer binders, and is compared with Example 7.
[0164] 1. Preparation of positive electrode film The positive electrode membrane was prepared in an argon-protected environment where the water and oxygen content were both below 1 ppm.
[0165] Using LiNi 0.8 Co 0.1 Mn 0.1 O2 was used as the high-nickel ternary cathode material. The high-nickel ternary cathode material, Li6PS5Cl solid electrolyte, conductive carbon, and polymer binder were weighed according to a mass ratio of 70:25:2:3. The polymer binder was PTFE.
[0166] The raw materials were dry-mixed at 300 r / min for 30 min and sheared at 60℃ for 20 min to form a fibrous bonded network of PTFE.
[0167] The mixture was subjected to three dry calendering processes at 80℃ and 100MPa to obtain a positive electrode film with an average thickness of 50μm.
[0168] 2. Electrode performance testing The electronic conductivity of the obtained positive electrode film was detected using the four-probe method, and the result was 1.4 S / cm.
[0169] 3. Preparation of solid electrolyte membranes Li6PS5Cl solid electrolyte and PTFE were dry-mixed at a mass ratio of 98:2 and pressed into a membrane at 80℃ and 100MPa to obtain a solid electrolyte membrane with a thickness of 80μm.
[0170] 4. Battery assembly and electrochemical testing The positive electrode membrane was cut to 20mm × 20mm and stacked with a Li6PS5Cl solid electrolyte membrane. A lithium metal negative electrode was then added to complete the assembly of the small pouch cell. An external pressure of 0.1MPa was applied to the resulting cell using a fixture.
[0171] The battery was tested for charge and discharge at 25°C, with a voltage range of 3.0V to 4.2V and a charge and discharge current of 350μA.
[0172] Test results show that the charging capacity in the first cycle is 182 mAh / g, the discharging capacity is 168 mAh / g, and the coulombic efficiency in the first cycle is 92%. After 50 cycles, the charging capacity is 157 mAh / g, the discharging capacity is 143 mAh / g, the coulombic efficiency in the 50th cycle is 91%, and the cycle maintenance rate is 85%.
[0173] Example 7 and Comparative Example 3 used the same positive electrode active material and solid electrolyte. The difference between the two is that Example 7 uses Al metal particles instead of conductive agents and binders, and includes solid electrolyte particles. A self-supporting composite positive electrode sheet is formed by the ductile deformation of the Al metal particles without the addition of conductive agents and binders. Comparative Example 3, on the other hand, relies on a conductive carbon and polytetrafluoroethylene fibrous bonding network to form the positive electrode film. The in-plane electronic conductivity of the electrode sheet in Example 7 is 27.2 S / cm, which is much higher than the 1.4 S / cm of Comparative Example 3, and the cycle retention rate after 50 cycles is 86%, which is higher than the 85% of Comparative Example 3.
[0174] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A composite positive electrode sheet for an all-solid-state battery, characterized in that, By mass percentage, it includes: 30%~50% positive electrode material particles, 20%~60% metal particles, and 10%~30% solid electrolyte particles.
2. The all-solid-state battery composite positive electrode sheet according to claim 1, characterized in that: The cathode material particles are selected from one or more of lithium battery cathode materials, sodium battery cathode materials, and carbon-supported sulfur materials; the lithium battery cathode materials include lithium nickel cobalt manganese oxide, lithium iron phosphate, and lithium manganese oxide; the sodium battery cathode materials include sodium sulfide, sodium nickel iron manganese oxide, sodium iron phosphate, and sodium ferrocyanate.
3. The all-solid-state battery composite positive electrode sheet according to claim 1, characterized in that: The metal particles are selected from one or more of Al, Sn, In, Bi, Mg, Cu, Fe, Ni, Zn and Mn, or alloys composed of two or more of these metal elements.
4. The all-solid-state battery composite positive electrode sheet according to claim 1, characterized in that: The solid electrolyte particles are selected from lithium battery electrolyte materials or sodium battery electrolyte materials.
5. A method for preparing an all-solid-state battery composite positive electrode sheet, used to prepare the all-solid-state battery composite positive electrode sheet as described in any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Provides cathode material particles, metal particles, and solid electrolyte particles; S2. Without adding liquid solvents, conductive agents, and polymer binders, the raw materials of the positive electrode material particles, the metal particles, and the solid electrolyte particles are dry-mixed to obtain a mixture; S3. The mixture is laid as a layer to be compressed, and the layer to be compressed is subjected to tableting to obtain a tablet blank; S4. The tablet blank is subjected to heat treatment until the tablet blank reaches the preset hot pressing temperature to obtain a heat-treated tablet; S5. At the preset hot pressing temperature, the heat-treated sheet is subjected to hot rolling at least twice to obtain a self-supporting composite positive electrode sheet for all-solid-state batteries.
6. The preparation method according to claim 5, characterized in that: The heat treatment temperature is 50℃~300℃; the pressure of the hot roll calendering is 10MPa~1000MPa.
7. The preparation method according to claim 5, characterized in that: The thickness of the composite positive electrode sheet is 5μm~100μm.
8. The preparation method according to claim 5, characterized in that: The four-probe electron conductivity of the composite positive electrode is ≥17 S / cm.